Performance Test of Commercial Air Coolers with Cooling Pads Made from Banana Midrib Fiber and Honeycomb - Sonawan, Hery; Sofia, R Evi (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2024)
The use of air conditioning equipment in dry season is very necessary. Several users have used Air Conditioner (AC) as air conditioning, although there are users who apply air coolers which are considered more environmentally friendly air conditioning. An air cooler is a tool that cool the air while increasing the humidity. This tool uses the principle of the water evaporation process to cool the air or is called an evaporative cooler. In this paper, the performance of a commercial air cooler that uses a built-in cooling pad in the form of honeycomb is reported and its performance is compared with a cooling pad made from banana midrib fiber material.By implementing experiments on commercial air coolers, experiments were carried out by measuring the airflow in the air cooler using Arduino-based data acquisition. From the experiments, the built-in cooling pad has better performance than banana midrib fiber. The decrease in airflow temperature when using a honeycomb cooling pad reaches 0.8 ℃, slightly higher than banana midrib fiber which reaches 0.6 ℃. Honeycomb saturation efficiency is also higher, reaching 50 – 85% compared to 40 – 70% for banana midrib fiber. Likewise, the EER value of honeycomb is higher than banana midrib fiber. However, banana midrib fiber has great potential if it is used as a cooling pad material, it can be used as an alternative material for evaporative coolers.